CONTAINER STORAGE AS AN ELEMENT OF ENHANCEMENT OF ENVIRONMENTAL SAFETY AND A STATE POLICY TOOL FOR DEALING WITH TECHNOLOGICALLY ENHANCED SOURCES OF IONIZING RADIATION - Reshetchenko А.; Iurchenko, V.; Kurakova, N.; Vorobiov О. (Municipal economy of cities. Series: «Economy science», 2023)
In order to implement the state environmental policy and ensure environmental safety, a number of normative legal acts, laws and state standards have been implemented on the territory of Ukraine. Special attention was paid to the State Targeted Environmental Program for the Management of Radioactive Waste, the main principle of which is the implementation of the protection of the population and the natural environment in order to create safe conditions for the existence of current and future generations and ensure sustainable development. The article highlights the results of research and development works on the development and certification of a set of packaging type IR-2 for the transportation and temporary storage of low- and medium-level solid radioactive waste KTTZ-NS-1-02.00.00, as a key element of environmental protection technologies during handling with radioactive waste. The urgent task of handling radioactive waste, which is caused by the accumulation of a significant amount of sludge in the territories of the oil and gas production complex enterprises and requires temporary storage and transportation, has been solved, as a prerequisite for increasing the efficiency of ensuring the environmental safety of the mentioned objects of formation. The technical characteristics of the packaging kit are described in detail, schematic drawings are provided, and the main parameters and dimensions of the developed packaging kit type IR-2 are provided. The scheme of the main stages of the testing of this packaging set and the certificates obtained as a result of such work, which were carried out jointly with representatives of the State Inspection of Nuclear Regulation, are presented. The developed packaging set significantly exceeds the performance of the packaging set currently used in temporary storage facilities.